When the body says no eaudiobook The cost of hidden stress. - Maté, Gabor (Vintage Canada, 2021)
INTERNATIONAL BESTSELLER From renowned mental health expert and speaker Dr. Gabor Maté, this acclaimed, bestselling guide provides insight into the mind-body link between illness and health, and the critical role that stress and our emotional makeup play in an array of common diseases. In this accessible and groundbreaking book—filled with the moving stories of real people—medical doctor and bestselling author Gabor Maté shows that emotion and psychological stress play a powerful role in the onset of chronic illness, including breast cancer, prostate cancer, multiple sclerosis, Alzheimer's disease and many others.   An international bestseller translated into over thirty languages, When the Body Says No promotes learning and healing, providing transformative insights into how illlness can be the body's way of saying no to what the mind cannot or will not acknowledge. With great compassion and erudition, Dr. Maté demystifies medical science and empowers us all to be our own health advocates.